Dermatomiositis: Case presentation - Yanelka Bouza Jiménez; Iliana de los Milagros Núñez Paredes; Yalaidy Pérez Rodríguez; Stephany Milagros Acosta País (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
A Clinical case of a 30 year old female patient who started by the end of January  2017 with intense  pain in the muscles of the four limbs which impeded her from her daily routines , muscular weakness and asthenia which progressed severely.  In addition, on interviewing antecedents of cutaneous lesions, problems at deglutition, dyspnea on exertion which disappeared at rest, cough with scarce whitish expectoration, ageusia, cervical pain and slight weight loss. She was admitted at the Internal Medicine ward and high values of Creatinine and Phosphokinase and other enzymes. An electromyography and a muscle and skin biopsies were performed.  In addition, itwas started a treatment with steroids and inmmuno-depressors which had a noticeable clinical improvement. As a result of the study the patient was diagnosed with dermatomiositis, one of the most frequent forms of inflammatory idiopathic myopathies. It progressed favorably, improving the symptoms and she was discharged with follow up by outpatient consultation